The effects of oxidative stress and innate immunity on European badger (Meles meles) life-history dynamics - Bilham, K (2016)
Wild animals are faced with many stressors from starvation to infections, which will affect individual survival and population dynamics. Free radicals and reactive oxygen species are involved in many of these processes, from cell signalling and immunity, to potentially being a causal factor in ageing. Oxidative stress is posited as a major factor in population dynamics, ultimately driving the evolution of life-history traits in wild species, acting as the 'currency' through which various trade-offs operate. In this thesis, I present a series of studies on the Wytham population of European badgers (Meles meles) focussed on dissecting the effects of host responses to stressors and pathogen recognition on life-history success. The first part of this thesis investigates intrinsic and extrinsic factors affecting oxidative stress and antioxidant defences, linked to population-dynamic effects and life-history traits. I model the crucial intrinsic (development, ageing, reproduction) and one important extrinsic (weather conditions) factors affecting oxidative stress levels in a wild mammal, in relation to survival and reproductive investment. Benefitting from a long term study with marked individuals of a known age, I found that cubs trade-off the development of antioxidant defences against growth, and that juvenile survival is dependent on levels of oxidative damage. These factors are interactive with prevailing yearly weather conditions; investment in antioxidant defences has the greatest survival benefit for young cubs in harsh years (dry, cold spring). I also show that weather affects age-classes in different ways, but I did not find any link between higher oxidative damage and ageing, even following individual responses. The second major focus for the thesis is to explore the immune capability of badgers, focussing on macrophage function and the initial recognition of pathogens. Wildlife immunology represents a "neglected area" of ecology that has potential for large impacts in terms of conservation and disease management. Indeed, wildlife can be a reservoir for infections that affect humans (zoonotic infections) and their livestock. The badger is a classic example of this effect being considered an important reservoir for Mycobacterium bovis, the cause of bovine tuberculosis (bTB). I employed molecular immunology methodologies to develop a methodological tool box to assess immune responses in badgers, which are then employed to investigate the response of blood monocyte-derived macrophages to microbial agonists that stimulate Toll-like receptors. The major findings are that badger macrophages fail to produce nitric oxide or meaningfully upregulate inducible nitric oxide synthase mRNA after exposure to TLR agonists, bacterial lysates and / or recombinant badger Interferon gamma. The TLR system is demonstrated to be largely intact in badger macrophages since exposure to TLR agonists did induce upregulation of cytokine mRNA. The only agonists that stimulated very low responses are those that target TLR9, but this was due to very low levels of expression of TLR9 mRNA. Both nitric oxide and TLR9 are implicated in responses to bTB and these deficiencies would significantly impact on the susceptibility of badgers to infection. There are numerous wider implications of my work: My thesis foremost highlights the importance of taking an integrated approach to eco-physiology and eco-immunology, as these processes are heavily intertwined. The weather correlates of oxidative stress not only highlight the potential vulnerability of all species to human induced rapid environmental change, but provide a stark warning especially for less resilient specialists. The immunology work confirms the importance of carefully analysing immune responses of wildlife species, especially in the context of designing effective species management strategies for diseases such as bTB, providing indicators of why a species may be susceptible to infection and indicating potential ways to improve vaccination.